4CPS-065 Adequacy of vancomycine dosage in the intensive care unit of a university hospital - Llinares-Esquerdo, M (Eur J Hosp Pharm, 2018)
BACKGROUND: Critically ill patients experience many pathophysiological changes that can affect the effectiveness of pharmacological treatment. PURPOSE: To describe the recommendations of dosage and monitoring of vancomycin used in the intensive care unit and to assess whether these are adequate to achieve optimal early therapeutic levels. MATERIAL AND METHODS: Retrospective observational study carried out from January to December 2016 in a hospital with 21 beds of critically ill patients. This unit did not use any specific guides for the dosage of the antibiotic therapy with vancomycin. For this reason, we assessed whether the initial dosage was ideal to achieve effective antibiotic levels. The following variables were collected from the program GestLab(®): sex, age, weight, dosage prior to the monitoring, time from the beginning of the treatment until the first monitoring, and time to target blood range levels. Finally, initial vancomycin trough serum level (Cv) was recorded by classifying it according to its relationship with the target therapeutic range in: in range (IR), overdose (OD) and underdose (UD). It was considered as optimum a therapeutic range concentration between 10 and 15 mcg/mL, except in some serious infections (as well as pneumonia, endocarditis, meningitis, osteomielitis, bacteraemia, sepsis or Methicillin-resistant staphylococcus aureus infections) in which Cv goals were 15 to 20 mcg/mL. RESULTS: One hundred and forty-eight determinations, for 58 patients who required intensive care and were treated with vancomycin, were recorded. In 69% of the cases, the treatment with vancomycin was initiated with a 1 g/12 hour dose, 24.1±7.1 (10–44) mg/kg/day, regardless of patient characteristics and type of infection. The time until the first determination was 2.4±1.4 (1–9) days. The target range was 10 to 15 mcg/mL in 69% of the cases. In the first control: 76% of the patients were UD, 14% OD and only 10% IR. The mean time to manage concentrations in the range was 5.3±2.2 (3–12) days, for which an average of 2.6±0.8 (2–5) determinations were required. To achieve concentrations in this range, a mean dose is required of of 29.9±18.5 (6.4–88.9) mg/kg/day. CONCLUSION: With the current dosage, three of every four first controls are UD, delaying the proper treatment of the infection. To avoid this, one could consider an initial load dose of vancomycin. Plasma levels of systematic monitoring can be very useful to achieve rank levels as soon as possible. REFERENCES AND/OR ACKNOWLEDGEMENTS: To our colleagues, thank you. No conflict of interest